PERAN GURU PAI DALAM MENINGKATKAN MINAT BACA AL QUR'AN PESERTA DIDIK DI SD NEGERI 3 PETUNGSINARANG - Siyus; Septyana Tentiasih (STIT Muhammadiyah Paciran, 2023)
The learning methods in PAI can influence students' desire to learn, which can improve their learning outcomes. This research aims to collect and collect data because learning activities will be successful only if students want to learn. This research uses qualitative methods and uses research instruments such as interviews, observations, and documentation. The results explain and provide an overview of how the learning method in PAI subjects at SD Negeri 3 Petungsinarang is carried out effectively and can increase the motivation of homeroom teachers to teach students. Teachers also teach students about the importance of preserving nature by using learning methods that are in accordance with students' interests in PAI, such as demonstrations with the media, discussions, and questions and answers. The results of the study show that the short time